VIGS en menslike gedrag: ’n Teologies-etiese beoordeling - Bruyn, P. J. de (Koers, 1990)
AIDS is a fatal disease which is at present incurable. It is spread mainly through extra-marital heterosexual and homosexual intercourse. The distinctive feature of AIDS is that it destroys the immunity system of the human body. The victim subsequently dies of any common disease. At present AIDS is spreading extremely rapidly: world-wide, the number of people contracting the disease is doubled every ten months. The most important ways in which AIDS is contracted and spread, can be ascribed to sinful actions and ways of living, because these patterns of conduct are forbidden by God. Firstly, this means that if sexual intercourse were practised within lawful matrimony according to God's will, AIDS would not be a threat of any significance. Secondly, it means that people contracting AIDS through a promiscuous lifestyle, should see the disease as a punishment of God. In those instances where AIDS is contracted in other ways, it should be regarded as a sore trial. AIDS sufferers should not be stigmatised or ostracised, but should be actively supported and helped, especially by the churches. The way in which Christians behave towards sufferers of AIDS should reflect the compassion and charity of Christ towards sinners.